Designing the French interior : the modern home and mass media - Lasc, Anca I.; Downey, Georgina; Taylor, Mark, 1955- (Bloomsbury Academic, 2015)
"Designing the French Interior traces France's central role in the development of the modern domestic interior, from the pre-revolutionary period to the 1970s, and addresses the importance of various media in representing and promoting French interior design to a wider audience. Contributors to this original volume identify and historicize the singularity of the modern French domestic interior as a generator of reproducible images, a site for display of both highly crafted and mass-produced objects, and the direct result of widely-circulated imagery in its own right. To this end, a variety of media and representational techniques are discussed side by side, including drawings, prints, pattern books, illustrated magazines, department store catalogs, photographs, guidebooks, and films. Structured into three parts and including chapters by leading scholars addressing a wide range of subjects, this book is intended to broaden understanding of French interiors, from historical, theoretical and practice-based perspectives, and provides an invaluable new understanding of the relationship between architecture, interior spaces, material cultures, mass media and modernity"--